BUSINESS STRATEGY DEVELOPMENT FOR SALSE LIVING - Chanra Satria Putra; Dona Saphiranti (Fakultas Ekonomi UNIBBA, 2024)
Every human being have to think creatively and able to innovate in his life in order not to fall behind by others. Creativity greatly affects someone's level of life, both socially and economically. Creativity can be implemented in every aspect of human life, including in economy aspects. Creative economy is one of the sectors that support the economy and the level of development of a country. Indonesian creative productivity index is Ranked 12th in Asia by Asian Development Bank in August 2014. Salse Living is a local start-up brand of home decoration product established on August 2014. Salse Living applied the original illustration in the form of medium that can have economic value. In the beginning, Salse Living only made illustrated cushion only, but in the process, the products are evolving into wider range of home decoration products. Unique illustration has become the character and identity in each of the products to become a differentiator from another competitor with similar service.The purpose of this study is to find the best business strategy to be implemented in following days. While finding the strategy, Salse Living is facing various issues that detain the business growth. The issues is coming from marketing, sales and distribution, human resources limitation, lack of publication, lack of innovation and product development, and unavailability of adequate office, workshop and showroom.To face the current business issues, Salse Living has several business solutions to be implemented. By using benchmark analysis on big companies such as IKEA for its business development and Donna Wilson for its product innovation and design. By benchmarking IKEA, the author can learn about how IKEA could sell the product with reasonable price. In the other hand, the author learned about the design from Donna Wilson product. Then, the author analyzes the external and internal factors that affects Salse Living's business situation to study the strengths, weaknesses, opportunities and threats through the SWOT analysis. Salse Living Strengths are illustration point, high quality product, hand made, custom design service, and customer relationship can be implemented to develop the company. While, Salse Living weakness such as limited human resource, limited budget, poor distribution and promotion have to be faced as Salse Living advanced strategies.Salse Living business strategies to increase selling and company publication are through online and offline marketing. For online market, the action can be implemented through Salse Living's partner e-commerce store, Instagram, and building company`s website. For offline market, the action can be implemented through attending more pop-up markets and cooperate with more partner stores